Modern Music and After: Directions since 1945 - Griffiths, Paul (Oxford Oxford University Press, 1995)
This fully revised new edition re-establishes Paul Griffiths's survey as the definitive study of music since the Second World War. The disruptions of the war, and the struggles of the ensuing peace, were reflected in the music of the time: in Pierre Boulez's radical re-forming of compositional technique and in John Cage's move into zen music, in Milton Babbitt's settling of the serial system, and in Dmitry Shostakovich's unsettling symphonies, in Karlheinz Stockhausen's development of electronic music and in Luigi Nono's pursuit of the universally human, in Iannis Xenakis's view of music as sounding mathematics and in Luciano Berio's consideration of it as language. The initiatives of these composers and their contemporaries opened prospects that have continued to unfold. This constant expansion of musical thinking since 1945 has left us with no single history of music. 'We live' as Griffiths says, 'among many simultaneous histories'. His study accordingly follows several different paths, showing how they converge and diverge. In addition to the composers mentioned above, others whose music is discussed include Steve Reich, Jean Barraque, Elliott Carter, Olivier Messiaen, Gyorgy Kurtag, Bill Hopkins, Harrison Birtwhistle and Gyorgy Ligeti. Publication and recording details are given for the works of all these composers and many others. For its breadth and for its wealth of detail, Modern Music and After will appeal to both student and the general reader in search of a lively and comprehensive introduction to the music of our time.
Keywords: 20th Century (1901-2000); Music history